L’analyse des relations entre minorités et majorités: Retour sur la situation néo-zélandaise à l’aube des années 2000 - Gagné, Natacha (Anthropologica, 2022)
This article falls within the tradition of works aiming to understand the relationships between minorities and majorities within a nation-state. As a case study, the author looks at the events that have happened in New Zealand since 2003, in particular the controversy concerning the ownership of the foreshore and seabed. She argues in favour of a detailed analysis of the relationships between minority and majority populations and their impacts on internal tensions, (non-)mobilization as well as on the development of ideologies. The analysis relies heavily on Eric Schwimmer’s work, in particular his definitions of the concepts "real competition" and "symbolic competition."